GREATER DISEASE BURDEN, GREATER RISK? EXPLORING COGNITIVE CHANGE AND HEALTH STATUS AMONG OLDER BLACKS. (11th November 2018) - Byrd, D; Thorpe, R; Whitfield, K
Abstract: Health disparities across multiple domains of health disproportionately impact Blacks compared to Whites. There is growing research that suggests that poor health and disease burden contribute to variability in cognitive functioning. We hypothesize that health will impact change in psychometric dimensions of cognition over time. Longitudinal data from the Baltimore Study of Black Aging-Patterns of Cognitive Aging were used to assess cognitive change over a 33 month interval in five domains; working memory, perceptual speed, verbal memory, vocabulary and inductive reasoning. The sample consisted of 602 community-dwelling blacks, aged 48–92 years at initial interview and 450 at the second interview. Co-morbidities were assessed using a summary of counts of chronic conditions (diabetes, CVD, hypertension, arthritis, stroke), which were dichotomized into having two or more conditions compared with one or none. Other measures of health included average peak expiratory flow and blood pressure. OLS was used to examine the relationships between measures of health and cognitive change, controlling for age, gender, education and baseline cognition. Findings indicated that a greater number of co-morbidities was associated with change in perceptual speed; whereby, Blacks with two or more conditions had significantly slower speed than those with one or no conditions (b=-5.099, p= 0.022). Average peak expiratory flow (a measure of lung functioning) was associated with changes in working memory (b=0.029, p= 0.019) and perceptual speed (b= 0.026, p= 0.026). These findings suggest that different aspects of health may impact specific domains of cognitive change in later life among Blacks.